Effective Financial Management Strategies to Improve MSME Performance - Hasanudin Hasanudin (SEAN Institute, 2023)
The purpose of this research is to find and analyse efficient financial management solutions for improving the performance of Micro, Small, and Medium Enterprises (MSMEs). A qualitative approach was adopted, utilising in-depth interview techniques and participant observation as a data gathering instrument. The research subjects were owners and managers of SMEs who have improved their financial performance in the previous three years. According to the findings of the study, there are three effective financial management strategies: (1) locating appropriate funding sources, (2) producing accurate budgetary reports, (3) managing capital structure, and (4) performance management. These techniques can assist MSMEs in improving their financial performance and dealing with the challenges of a complicated and changing business environment. This study is expected to contribute to the advancement of MSME financial management theory as well as provide practical recommendations to MSME owners and managers on how to enhance their financial performance.